Canada’s gross domestic product per capita: Perspectives on the return to trend - Carter McCormack; Weimin Wang (Economic and Social Reports)
This article provides perspectives on the extent to which recent changes in gross domestic product per capita represent a departure from their long-term trend and discusses factors that have facilitated per capita growth in previous decades.